Intrasectoral Structural Convergence of the Economies of Bulgaria and Romania to the Eurozone - Damyanov, Dimitar (Research Papers, 2021)
Convergence of production structures is an important factor for the synchronization of the business cycles of Eurozone economies and for the effectiveness of the monetary policy of the ECB. This paper presents an analysis of the process of structural convergence between the economies of Bulgaria, Romania and the Eurozone at the intrasectoral level for the period 1998 – 2017. A sigma convergence methodology is employed, and the divergence index and dissimilarity index are applied. The results indicate that production structures in Bulgaria are diverging slightly from the Eurozone, while the opposite is true about Romania.